The effect of high oral loading dose of cholecalciferol in non-alcoholic fatty liver disease patients. A randomized placebo controlled trial - Amal Ahmed Mohamed; Ahmed Abdel Halim; Sahar Mohamed; Seham Mohamed Mahmoud; Eman Mohamed Bahgat Eldemiry; Rasha Sobh Mohamed; Mahmoud Maamoun Shaheen; Gina G. Naguib; Nashwa M. Muharram; Mona G. Khalil; Salma Saed; Randa Ibrahim; et al. (Frontiers in Pharmacology, 2023)
Background and Aim: Non-alcoholic fatty liver (NAFLD) is one of the most common progressive metabolic disorders worldwide. There are increasing scientific interests nowadays for the association between vitamin D status and Non-alcoholic fatty liver. Earlier studies have revealed that vitamin D deficiency is highly prevalent in Non-alcoholic fatty liver patients that contributes to poor outcomes. Hence, the present study aimed to assess the efficacy and safety of oral cholecalciferol on Non-alcoholic fatty liver patients.Subjects and Methods: This study was conducted on 140 patients that were randomized either to group 1 that received the standard conventional therapy in addition to placebo or group 2 that received the standard conventional therapy in addition to cholecalciferol during the 4 months study period.Results: At the end of the study group 2 revealed significant decrease (p < 0.05) in the mean serum level of TG, LDL-C, TC, hsCRP as compared to their baseline results and group 1 results. Additionally, a significant improvement in the serum levels of ALT (p = 0.001) was seen in group 2 at the end of the study when compared to group 1. Whereas group 1 did not show any change in these parameters when compared to group 2 and their baseline results.Conclusion: Cholecalciferol was shown to have beneficial effects on serum ALT levels, hsCRP levels and lipid profile of NAFLD patients.Clinical Trial Registration:https://prsinfo.clinicaltrials.gov/prs-users-guide.html, identifier NCT05613192